Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Materi FPB dan KPK Kelas 4 SD Negeri 1 Nalumsari - Wardani, Anggun Septi (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2020)
Many students have difficulty in solving math story problems. These difficulties are expressed by making mistakes in solving cheerful mathematical problems. Difficulties and errors of students in solving math story problems must be minimized. This can be done if the teacher knows the mistakes made by students and made efforts to overcome the difficulties of students in solving math story problems. This study aims to describe the difficulties and errors of students in solving mathematical story problems and the teacher's efforts in overcoming student difficulties. The method used in this research is qualitative with a descriptive approach. The study was conducted at SDN 1 Nalumsari and the subjects studied were high class students namely class IV, VdanVI. Data collection is done by using test, interview, observation and documentation techniques. Based on the results of the analysis conducted, the difficulty of high class students in solving math story problems is (1) lack of mastery of concepts (2) lack of interest in mathematics lessons (3) do not understand the purpose of questions (4) rarely do exercises (5) afraid to ask the teacher if you have difficulty (6) do not concentrate when the teacher explains. While students' mistakes in completing mathematical story problems include (1) errors in calculation as much as 33% of class IV, 21% of class V, 48% of class VI (2) errors do not write math sentences 24% of class IV, 56% of class V (3) incomplete work as much as 5% of class V and 5% of class VI (4) errors do not write down units as much as 43% of class IV.